2023
DOI: 10.3389/fpsyt.2023.1186138
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ICD-11 and DSM-5 criteria of PTSD among Chinese trauma-exposed adolescent samples

Abstract: This study aimed at comparing the prevalence and comorbidity differences of PTSD according to ICD-11 and DSM-5 definitions across two Chinese adolescent trauma-exposed samples. A total of 1,201 students exposed to earthquake and 559 students from vocational schools exposed to potentially traumatic events were included in this study. The PTSD Checklist for DSM-5 was used to measure PTSD symptoms. The MDD and GAD subscales of the Revised Children’s Anxiety and Depression Scale were used to measure major depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
(38 reference statements)
2
2
0
Order By: Relevance
“…Additionally, most participants who met the criteria for PTSD also met the criteria for MDE or GAD, which is also consistent with past research (Bruckmann et al, 2020;Hyland et al, 2016;Wang et al, 2023). However, in the present study, comorbidity rates were not substantially different across the three PTSD classifications.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Additionally, most participants who met the criteria for PTSD also met the criteria for MDE or GAD, which is also consistent with past research (Bruckmann et al, 2020;Hyland et al, 2016;Wang et al, 2023). However, in the present study, comorbidity rates were not substantially different across the three PTSD classifications.…”
Section: Discussionsupporting
confidence: 91%
“…A comparison of these diagnostic systems revealed a moderate overall level of agreement between the two diagnoses, with DSM-5 PTSD more prevalent than ICD-11 PTSD. The study findings are consistent with prior research with higher-risk or clinical samples of trauma-exposed youth that have found a higher prevalence of DSM-5 PTSD compared to ICD-11 PTSD (La Greca et al, 2017;Sachser et al, 2018Sachser et al, , 2022Wang et al, 2023) and that agreement between classification systems varied from low to substantial (Danzi & La Greca, 2016;La Greca et al, 2017;Sachser et al, 2018Sachser et al, , 2022Wang et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations